Fertility Preservation in Oncological Patients - Simona Zaami; Michael Stark (Clinical and Experimental Obstetrics & Gynecology, 2022)
Background: Lately, attention is given to fertility preservation in reproductive-age patients undergoing oncological treatment. This should become a routine part of today’s assisted reproductive technologies. Methods: Available oncofertility preservation methods, next to their clinical, ethical and legal implications are discussed, within the context of the right to health and its broader aspects as delineated in the 1946 Constitution of the World Health Organization. Results: Possible egg and sperm freezing. as well as ovarian tissue cryopreservation, should always be explained and suggested to fertility-age patients before starting oncological treatment. Sperm, oocyte, and embryo cryopreservation should become standard practice. Conclusions: All ethical, cultural, and moral aspects of fertility preservation in cancer patients are multifaceted and need to rely on principles that are based on widely-accepted guidelines and evidence-based practices. Adequate policy, legislation, and regulations should be agreed upon and implemented.